Windthrows control biomass patterns and functional composition of Amazon forests - Magnabosco Marra, Daniel; Trumbore, Susan E.; Higuchi, Niro; Ribeiro, Gabriel H. P. M.; Negrón‐Juárez, Robinson I.; Holzwarth, Frederic; Rifai, Sami W.; Santos, Joaquim; Lima, Adriano J. N.; Kinupp, Valdely F.; Chambers, Jeffrey Q.; Wirth, Christian (Global change biology, 2018)
Amazon forests account for ~25% of global land biomass and tropical tree species. In these forests, windthrows (i.e., snapped and uprooted trees) are a major natural disturbance, but the rates and mechanisms of recovery are not known. To provide a predictive framework for understanding the effects of windthrows on forest structure and functional composition (DBH ≥10 cm), we quantified biomass recovery as a function of windthrow severity (i.e., fraction of windthrow tree mortality on Landsat pixels, ranging from 0%–70%) and time since disturbance for terra‐firme forests in the Central Amazon. Forest monitoring allowed insights into the processes and mechanisms driving the net biomass change (i.e., increment minus loss) and shifts in functional composition. Windthrown areas recovering for between 4–27 years had biomass stocks as low as 65.2–91.7 Mg/ha or 23%–38% of those in nearby undisturbed forests (~255.6 Mg/ha, all sites). Even low windthrow severities (4%–20% tree mortality) caused decadal changes in biomass stocks and structure. While rates of biomass increment in recovering vegetation were nearly double (6.3 ± 1.4 Mg ha−1 year−1) those of undisturbed forests (~3.7 Mg ha−1 year−1), biomass loss due to post‐windthrow mortality was high (up to −7.5 ± 8.7 Mg ha−1 year−1, 8.5 years since disturbance) and unpredictable. Consequently, recovery to 90% of “pre‐disturbance” biomass takes up to 40 years. Resprouting trees contributed little to biomass recovery. Instead, light‐demanding, low‐density genera (e.g., Cecropia, Inga, Miconia, Pourouma, Tachigali, and Tapirira) were favored, resulting in substantial post‐windthrow species turnover. Shifts in functional composition demonstrate that windthrows affect the resilience of live tree biomass by favoring soft‐wooded species with shorter life spans that are more vulnerable to future disturbances. As the time required for forests to recover biomass is likely similar to the recurrence interval of windthrows triggering succession, windthrows have the potential to control landscape biomass/carbon dynamics and functional composition in Amazon forests. Windthrow severity and time since disturbance explain a large portion of observable variations in biomass patterns and functional composition across Central Amazon forests. Biomass stock in windthrown areas is drastically reduced and although rates of biomass increment in recovering vegetation are nearly double those of old‐growth forests, biomass loss due to post‐windthrow mortality is also high and unpredictable. Biomass recovery from windthrows takes up to 40 years and the recovery of the functional composition typical for old‐growth forests dominated by species with high wood densities is likely to take much longer than four decades.